Fitness-Related on Health Mobile Applications during COVID-19: Case of Turkey - Mumcu, Hasan Erdem (Progress in Nutrition, 2021)
Study Objectives: This study aimed to determine the usage status of Turkish infrastructure applications in the range of 4.5-5.0 points collected under the title fitness, health, and exercise in the Android Operating System Google Play Store application during the COVID-19 pandemic process.  Methods: The usage cases of mobile fitness, health, and exercise applications used by people were collected according to document analysis. Statistical analyzes were made using the SPSS 24 statistical program. Result: There were 95 applications scored in the range of 4.5-5.0 points. 56% of the applications were paid and 44% were free. 35% of users preferred free and 65% paid applications. While the first application on the market was released in 2010, the last application was released in 2020. There were 72 applications released before COVID-19 and 23 applications released after. The number of downloads over the determined score of the applications was 5.0 points 0.5%, 4.9 points 39%, 4.8 points 40%, 4.7 points 8%, 4.6 points 8%, and 4.5 points 5%. Within the application, only applications for males were 20.21%, applications for females only 28.27% and applications for both males and females were 48.51%. It was determined that the usage of mobile sports applications increased during the COVID-19 pandemic. It was observed that the usage rate of females was higher than the rate of males. It was determined that most applications were in the "health and fitness" category according to the restriction status within the platform, and the use of paid applications was more than free ones. Conclusion: It was thought that the applications to be produced on such digital platforms to protect and increase the level of physical activity of people under epidemic diseases and similar conditions were more comprehensive and encouraging to prevent various physical, psychological, and mental negative effects of sedentary life.